2018
DOI: 10.1093/jbcr/irx058
|View full text |Cite
|
Sign up to set email alerts
|

Burn Survivor Quality of Life and Barriers to Support Program Participation

Abstract: After a serious burn, re-entry into family life, society, and work can be incredibly difficult. Support services such as professional counseling and peer support play a key role for recovering survivors. Herein, we sought to identify support service participation rates, barriers to participation, and quality of life (QOL) among burn survivors treated at a regional burn center. A survey of burn survivors over 18 years old treated for a burn for 5 days or greater between 2006 and 2016 were invited to participate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Patients with burns over a lower TBSA reported better patient‐reported outcomes 2 years after burn injury. This finding is consistent with Baldwin et al, 24 who found that lower scores on selected quality of life scales were associated with burns of more than 30%. Patients with severe burn injury always experience physical symptoms such as pain, sensitivity and itching, together with psychosocial difficulties, such as anxiety, body image distress and difficulties in work, romantic relationships and intimacy 25 .…”
Section: Discussionsupporting
confidence: 91%
“…Patients with burns over a lower TBSA reported better patient‐reported outcomes 2 years after burn injury. This finding is consistent with Baldwin et al, 24 who found that lower scores on selected quality of life scales were associated with burns of more than 30%. Patients with severe burn injury always experience physical symptoms such as pain, sensitivity and itching, together with psychosocial difficulties, such as anxiety, body image distress and difficulties in work, romantic relationships and intimacy 25 .…”
Section: Discussionsupporting
confidence: 91%
“…We identified that logistical challenges (e.g., geographical distance and scheduling difficulties) act as barriers to participation in peer support programs, but are mitigated by facilitators such as a common background and/or sense of identity between mentors and partners [ 12 ]. Furthermore, previous studies in other disease populations have identified barriers and facilitators to participation in peer support programs that overlap with many of the themes that emerged in the current study [ 35 37 ]. However, the need for clear expectations for both mentees (partners) and mentors, identified by our key informants as a major theme in this study, has not been previously reported.…”
Section: Discussionmentioning
confidence: 68%
“…This study builds on a previously published study, 34 which contacted 968 adult burn survivors who were treated over a 10-year period to fill out QOL surveys. Out of 150 patients who completed the surveys, 67 offered to participate in interviews.…”
Section: Methodsmentioning
confidence: 99%